Intimate Partner Communication From the War Zone: A Prospective Study of Relationship Functioning, Communication Frequency, and Combat Effectiveness. (23rd September 2013) - Cigrang, Jeffrey A.; Wayne Talcott, G.; Tatum, JoLyn; Baker, Monty; Cassidy, Daniel; Sonnek, Scott; Snyder, Douglas K.; Balderrama‐Durbin, Christina; Heyman, Richard E.; Smith Slep, Amy M.
<x xml:space="preserve">Abstract</x> This study examined (a) the association between relationship functioning prior to and during deployment, and the frequency of communication during deployment; and (b) the association between relationship functioning and depression during deployment and their influence on service members' ratings of duty performance. Participants were 144 partnered Airmen assessed immediately before and during a one‐year high‐risk deployment to Iraq. Results showed an overall high frequency of partner communication during deployment. High relationship distress at predeployment predicted lower frequency of communication during deployment. Changes in relationship distress from before deployment to during deployment independently predicted frequency of communication, above and beyond predeployment distress levels. Level of relationship distress and depression during deployment independently predicted service members' ratings of impact on duty performance.